TEORI-TEORI ETIKA PERILAKU BISNIS DAN PANDANGAN ISLAM TENTANG PERILAKU ETIKA BISNIS - Rinol Sumantri, Rinol Sumantri Rinol Sumantri (I-Economics, 2015)
This conceptual papers intend to explores the ethical theories of business behavior and also devoted to explores Islamic view points of it. This papers argues that the study on business ethic has became an official  discipline on scientis circles. But, in addition to islamic points of view the study on business ethic behaviors had not fully well constructed as the official theory. In other words, so far the Islamic business ethics still on normative form, not well constructed yet. Its doesnt means that the reveletion norms was not sufficients, but the own conception is not adequate. Finally, this papers suggests that to be well constructed the islamic business ethics has to built a bridge between the reveletion ethics and rational ethics. Key Words:  Ethical Theories, Ethical Business Behavior, and Islamic View Points